Syrians under Temporary Protection and Their Acquision of Turkish Citizenship - Zeynep Derya Tarman (Annales de la Faculté de Droit d’Istanbul)
This paper describes possible ways of acquiring Turkish citizenship in relation to those Syrians in Turkey who are under temporary protection status. The paper initially provides an overview of the types of international protection statuses under Turkish law following which temporary protection status is examined. Next, the Turkish Citizenship Act is analyzed through the status of Syrians in Turkey. In this regard, initially, the acquisition of Turkish citizenship through kinship and general neutralization are explained, following which exceptional ways of acquisition is elaborated upon. Then, acquiring Turkish citizenship through marriage is explained which is followed by the final section on acquisition of Turkish citizenship through adoption. In providing such explanations, Council of State decisions that reflect the discretionary powers of the administrative authorities as well as the interpretations under the doctrine are taken into account. While certain particularities and restrictions under the relevant laws exist and the discretionary powers of the administrative authorities as well as Turkish public policy concerns may cause obstacles, the Turkish Citizenship Act provides possible legal grounds for the naturalization of Syrians under temporary protection in Turkey.